Strategi Penanganan Risiko Operasional Pemasaran Beras Pada Umkm Selaras Makmur Trijaya - Widya Puspita Sari; Gusganda Suria Manda (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2021)
Rice in Indonesia is positioned as a strategic commodity, both from an economic and socio-political perspective, because rice is a staple food for 95% of Indonesia's population, providing employment opportunities and a source of income for around 21 million farm households, and around 30% of the total expenditure of poor households. allocated for rice. Micro, small and medium enterprises (MSMEs) are businesses that play an important role in the national economy. At this time, MSMEs are intensively run in various regions in Indonesia. One of the regions that run the business is Karawang, one of which is in the rice marketing business. Marketing strategy is a form of plan to determine the success of a company in marketing its products. UMKM Selaras Makmur Trijaya is one of the rice mills. These businesses want to expand their market share. Therefore, the right marketing strategy is needed from the results of understanding the strengths and weaknesses, as well as opportunities and threats to expand the distribution area beyond its territory. risk identification is the first step to identify operational marketing problems in the downstream tea industry of PTPN VIII. By using the Z-Score and Value at Risk (VAR) Method, it will show the results of the probability and impact of operational risk marketing. Preventive and mitigation strategies can handle this company for the expected sales growth up.